Hericium erinaceus powder inhibits the growth of Porphyromonas gingivalis - Hirono Ichikawa; Junya Kawai; Koichiro Mori (Open Journal of Bacteriology - Peertechz Publications, 2021)
Disruption of the oral microbiota may contribute to the pathogenesis of oral diseases such as gingivitis. It is desired to explorer for a natural material that is safe for the body and specifically suppresses the growth of periodontopathic bacteria. Hericium erinaceus, which is consumed as food or used as a herbal medicine in East Asia, has been previously reported to inhibit bacterial growth. However, few studies addressed its effects on oral bacteria. Here we determined the effects of H. Erinaceus Powder (HEP) on the periodontal pathogenic bacterium Porphyromonas gingivalis and a nonpathogenic commensal bacterium Streptococcus gordonii. The antibacterial activity of HEP were evaluated by colony forming unit assay. As a result, HEP significantly inhibited the growth of P. gingivalis in a concentration-dependent manner, but in contrast, did not exhibited significant antibacterial activity against S. gordonii. H. erinaceus may selectively inhibit the growth of P. gingivalis and be useful for prevention of periodontal disease.